ARTIFICIAL INTELLIGENCE IN DEVELOPING FOREIGN LANGUAGE LEARNING AND STRATEGIC COMPETENCE FOR HIGHER EDUCATION STUDENTS - Konotop, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This article highlights the relevance of developing learning and strategic competence in higher education students amidst the digitalization of education and the potential of artificial intelligence for its advancement. It substantiates the contradictions between societal needs and the insufficient development of methodologies for fostering this competence using artificial intelligence. The aim is to illuminate the potential and identify key directions for fostering students’ learning strategy competence through artificial intelligence technologies. Five key application areas of artificial intelligence are distinguished: adaptive systems, intelligent feedback, virtual assistants, learning analytics, and time management systems. The effectiveness of artificial intelligence in enhancing metacognitive awareness is confirmed. Conclusions are drawn regarding the key factors for artificial intelligence’s effectiveness, and prospects for future research are outlined.